PENGAWASAN INFRASTRUKTUR JALAN OLEH DINAS PEKERJAAN UMUM KOTA PEKANBARU - Marwanaya, Robi; Rusli. SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Increasing the sheer number of residents and the boom the number of vehicles in the city of Pekanbaru is increasingly require adequate infrastructure support mainly in order to improve road infrastructure development, the Government of Pekanbaru City through the Department of Highways and Water Resources Pekanbaru for more attention to the condition of the road - the road existing as well as monitoring the roads - roads in the city of Pekanbaru. Where there are still many roads are damaged and not repaired so as to disturb the comfort of road users.The problem in this research is how the supervision of road infrastructures by the Department of Highways and Water Resources Pekanbaru city, as well as the factors - factors inhibiting the supervision of road infrastructure.The researchers used theoretical concept which adopted the theory of supervision by Manullang. The method used in this research is descriptive qualitative data collection instrument includes interviews with employees monitoring section of Highways and Water Resources Pekanbaru and society, observation and document data.The results showed that the implementation of road infrastructure supervision by the Department of Highways and Water Resources Pekanbaru is still not optimal. It is seen from the results of interviews and observations that researchers do in the office of the Department of Highways and Water Resources Pekanbaru, and coupled with public opinion revealed that the work of Highways and Water Resources was Pekanbaru is less satisfactory for them, because according to they still lack the performance conducted by the Department of Highways and Water Resources during thisPekanbaru.Keywords: Monitoring and Road Infrastructure